THE RELATIONSHIP BETWEEN STRESS DURING THE COVID-19 PANDEMIC AND THE INCIDENCE OF RECURRENT APHTHOUS STOMATITIS - Afryla Femilian; Khulia Furaida; Afina Hasnasari Heningtyas (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Recurrent Aphthous Stomatitis (SAR) is a common condition characterized by recurrent small, round, or ovoid multiple ulcers with clear boundaries and forming circles. The etiology of SAR is not yet clear, but some literature says SAR can be caused by psychological stress. Environmental changes and re-adaptation during the COVID-19 pandemic can affect stress levels. Materials and Methods: The type of research conducted is analytical observational studies with a cross-sectional design. The research sample was 226 respondents of the undergraduate dental program at the University of Muhammadiyah Yogyakarta (UMY) class of 2019, 2020, 2021. Each respondent filled out the RASDX questionnaire to find out the existence of SAR and the PSS-10-C questionnaire to assess stress levels in the form of a google form. Then, the data was analyzed using SPSS version 20 with a contingency coefficient test to see the relationship between stress during the COVID-19 pandemic and the incidence of SAR. Results and Discussion: The results showed that the majority of respondents were positive for SAR (20.3%). A total of 12 male respondents were positive for SAR (5.4%) and 34 female respondents were positive for SAR (15%). Measurements of stress levels attributed by the COVID-19 pandemic showed the majority of respondents experienced moderate stress (63.7%). A total of 12 respondents with mild stress, 33 respondents with moderate stress, and 1 respondent with severe stress were positive SAR. The results of the contingency coefficient test showed a value of p = 0.334. Conclusion: There is no relationship between stress during the COVID-19 pandemic and the incidence of SAR. This is thought to be because the causative factors of SAR are multifactorial.